2013
DOI: 10.1021/ie302231g
|View full text |Cite
|
Sign up to set email alerts
|

Insulation by Solution 3-Mercaptopropyltrimethoxysilane (MPS) Coating: Effect of pH, Water, and MPS Content

Abstract: We have investigated the effect of 3-mercaptopropyltrimethoxysilane (MPS) concentration, water content, and pH on the thickness and insulation quality of a MPS coating layer on a gold electrode obtained in an MPS solution in ethanol. We showed that controlling the MPS concentration, water content, and pH were all important for the insulation coating. With 1% MPS and 0% water, the coating rate remained well below 1 nm/h at all pH and at 2 and 8 nm/h in 0.1% MPS with 0.5% water at pH 9 and in 1% MPS with 1% wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The condensation of MPS in aqueous ethanol solution at high pH provides that the functionalized sensor surface is more compact than the coating with non‐condensed MUA . In the study of Oh et al ., it was reported that Protein G molecules in a solution form cloud‐like structures, and they are adsorbed onto a bare Au surface as a clustered pattern .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The condensation of MPS in aqueous ethanol solution at high pH provides that the functionalized sensor surface is more compact than the coating with non‐condensed MUA . In the study of Oh et al ., it was reported that Protein G molecules in a solution form cloud‐like structures, and they are adsorbed onto a bare Au surface as a clustered pattern .…”
Section: Resultsmentioning
confidence: 99%
“…Even though MPS coating results in a uniform protein G layer on the sensor surface, the BSA layer on MPS and pH reduces the cell binding. Also MPS is pH, coating repetition and time sensitive that makes it difficult to control the surface uniformity .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For electrical insulation, we followed an optimized wetchemical deposition method developed by Soylu et al 43 First, a PEPS was cleaned in a 1-in-40 diluted piranha solution (piranha solution is a 3:1 mixture of sulfuric acid and 30% hydrogen peroxide) for 10 min followed by de-ionized (DI) water and ethanol rinsing. It was then soaked in a 0.1 mM mercaptopropyltrimethoxysilane (MPS) (Sigma) solution in ethanol (Fisher) with 0.1% DI water for 30 min followed by soaking in a 0.1% MPS solution in ethanol with 0.5% DI water at pH 9 for 48 h where the MPS solution was replaced with a fresh one every 12 h. For each MPS solution replacement, the PEPS was first rinsed with DI water and followed by ethanol before immersing in a fresh MPS solution.…”
Section: Electrical Insulationmentioning
confidence: 99%